Immigration and challenges of multicultural Europe - Goycoechea, Alba (2016)
This article analyzes how Europe has started the new century con-fronting the challenge of conciliating the enormous flow of immigrants, coming from Third World countries and Eastern Europe, with its process of political and economic integration. The achievement of this conciliation, according to the author, poses the problem of establishing a multicultural environment within the hegemonic project of the European Union.